Marine litter from circalittoral and deeper bottoms off the Maltese islands (Central Mediterranean) - MIFSUD, R.; DIMECH, M.; SCHEMBRI, P.J. (Mediterranean Marine Science, 2013)
During the 2005 leg of the MEDITS trawl survey, benthic anthropogenic debris around the Maltese Islands (central Mediterranean) was quantified for the first time, with the aim of studying its abundance and distribution in the area. 357 items were sampled from 3.5 km2 of swept area. Each item was recorded, measured and its planar and surface areas were estimated. Plastic (47%), metal and glass (13% respectively) were the most prevalent types of litter in terms of number. Limestone slabs, sacks and fabric were the items with the highest planar and surface area per item. This suggests that it is also important to consider the size of debris items as well as numerical abundance in assessing impact of litter on benthic organisms. An attempt was made to correlate anthropogenic and environmental variables, including fishing activities and wave parameters, to litter abundance and distribution but no interpretable correlations were found, implying that litter abundance and distribution depends on factors other than those considered.